Who’s Who in Zoology: transversal application of gamification and new technologies in university teaching - Galan-Elvira, Jaime; Palau-Irisarri, Pablo (Frontiers in Veterinary Science, 2025)
IntroductionIn today’s hyperstimulating digital environment, shaped by social media and artificial intelligence, education struggles to retain students’ attention. Traditional teaching models risk obsolescence if they fail to adapt to rapidly evolving societal dynamics. However, this context offers an opportunity to innovate while maintaining academic rigor.MethodsTo enhance student engagement and modernize the learning experience, we implemented various gamification tools in the Biology course of the Veterinary Medicine degree. Strategies included a zoology-themed version of the classic game “Who’s Who?”, the use of the Kahoot! platform to review practical content, and interactive sessions designed to promote debate and teamwork in solving complex problems. The impact of these methods was assessed through academic performance data and student surveys focusing on engagement, knowledge acquisition, subject interest, and perceptions of the teaching team.ResultsThe introduction of gamified teaching strategies yielded highly positive results. Students reported increased motivation, deeper interest in the subject matter, and a more favorable perception of the teaching team. Moreover, a clear improvement in academic performance was observed, with higher average grades compared to previous years.DiscussionOur findings support gamification as a valuable tool in higher education, particularly in science-based courses. By aligning teaching methods with students’ expectations and cognitive habits, educators can improve both learning outcomes and classroom dynamics. Gamification offers a means to deliver rigorous content in an engaging format, helping bridge the gap between traditional education and today’s fast-paced, digital society.